Impact of yeast-fermented soybean waste on broiler growth and carcass quality - Malahubban, Masnindah; Leong, Sui Sien; Hassan, Mohammad Nasir; Kamaludeen, Juriah; Ab Aziz, Zakry Fitri; M. A., Azemi (Malaysian Society of Animal Production, 2024)
This study evaluated the effects of supplementing broiler diets with yeast-fermented soybean waste on growth performance and carcass characteristics. Ninety-nine three-week- old Ross-308 broiler chickens were assigned to three dietary groups: T1 (control diet), T2 (basal diet with fermented soybean waste without yeast), and T3 (basal diet with yeast- fermented soybean waste). From weeks 3 to 6, the fermented soybean waste either with yeast (T3) or without (T2) replaced 50% of the conventional soybean meal in the diet. At the end of the study, the chickens were slaughtered and analysed. Results indicated that final live body weight was similar (P > 0.05) between chickens on the yeast-fermented diet (T3) and those on the control diet (T1), while chickens on the non-yeast-fermented diet (T2) showed a significantly lower final body weight (P < 0.05) than the control group. By week 6, the feed conversion ratio (FCR) was significantly higher (P < 0.05) in both the T2 and T3 groups compared to the control. Notably, chickens on the T3 diet had significantly heavier breasts, drumsticks, and wings (P < 0.05) than those on the control diet. Overall, the inclusion of yeast-fermented soybean waste in broiler diets demonstrated potential as a partial substitute for soybean meal during the grower phase, offering a viable strategy to support sustainable and efficient protein sources in poultry production.